ANALISIS KESANTUNAN BERBAHASA PADA NOVEL “ME AND MY HEART” KARYA EVA RIYANTI LUBIS - Asep Solihin; Junita Junita; Sary Sukawati (IKIP Siliwangi, 2019)
This research is motivated by the fact that the principle of politeness is important both in oral and written. Novels as writing must also use levels and conversations that include the principle of politeness in language. The problems in this study are;